2007
DOI: 10.1002/chem.200601751
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis, Structure and Reactivity of B(C6F5)3‐Stabilised Amide (MNH2) Complexes of the Group 4 Metals

Abstract: Treatment of the homoleptic titanium amides [Ti(NR(2))(4)] (R=Me or Et) with the Brønsted acidic reagent H(3)NB(C(6)F(5))(3) results in the elimination of one molecule of amine and the formation of the four-coordinate amidoborate complexes [Ti(NR(2))(3){NH(2)B(C(6)F(5))(3)}], the identity of which was confirmed by X-ray crystallography. The reaction with [Zr(NMe(2))(4)] proceeds similarly but with retention of the amine ligand to give the trigonal-bipyramidal complex [Zr(NMe(2))(3){NH(2)B(C(6)F(5))(3)}(NMe(2)H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 93 publications
(56 reference statements)
1
52
1
Order By: Relevance
“…Closer inspection of 8⋅ 4(thf) reveals that the structural parameters of the two amidoborane ligands are very different. The Hf1N11B12 angle is 122.05(17)°, which, while more obtuse than the tetrahedral ideal, is smaller than the value of 135.14(17)° found for [Cp 2 Hf(Me){NH 2 B(C 6 F 5 ) 3 }], in which the steric demands of the borane fragment is greater 17. In contrast, the Hf1N41B42 angle is only 90.98(15)°.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Closer inspection of 8⋅ 4(thf) reveals that the structural parameters of the two amidoborane ligands are very different. The Hf1N11B12 angle is 122.05(17)°, which, while more obtuse than the tetrahedral ideal, is smaller than the value of 135.14(17)° found for [Cp 2 Hf(Me){NH 2 B(C 6 F 5 ) 3 }], in which the steric demands of the borane fragment is greater 17. In contrast, the Hf1N41B42 angle is only 90.98(15)°.…”
Section: Resultsmentioning
confidence: 63%
“…The structure of 3 b (Figure 3) is related to that of [([12]crown‐4)Li{NH 2 B(C 6 F 5 ) 3 }] 17. The reduced steric constraints lead to a closing of the LiNB angle from 121.35 to 114.32° and a shortening of the LiN bond length from 2.048 to 2.015 Å.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[143] Related bridged anions of the type [( F RO) 3 Al(m-X)Al-(OR F ) 3 ] À (where X = Cl or OH) are also accessible,b ut are more prone to either exchange reactions and/or dissociation to yield the corresponding [XAl(OR F ) 3 ] À and Al(OR F ) 3 species. [154] Additionally, the bridged WCAs[ (C 6 F 5 ) 3 E-F-E(C 6 F 5 ) 3 ] À (where E = Al or Ga) were shown to be formed by the reaction of the corresponding Lewis acid E(C 6 F 5 ) 3 with an appropriate stoichiometry of FCPh 3 to form the [CPh 3 ] + salts.F urthermore,the [CPh 3 ] + salt of the doubly bridged dianionic WCA [{(C 6 F 5 ) 3 Al} 3 -(m-F) 2 ] 2À featuring an AlÀFÀAlÀFÀAl linkage was also reported and in conjunction with the aforementioned WCAsi nvestigated as co-catalysts for sterospecific olefin polymerization. Bochmann and co workers reported the cyanide-bridged [(F 5 C 6 ) 3 B-CN-B(C 6 F 5 ) 3 ] À as well as the related dianionic [M{CNBC 6 F 5 ) 3 } 4 ] 2À (M = Ni or Pd) species and demonstrated their ability to support extremely rapid ethene polymerization.…”
Section: Bridged Wcasmentioning
confidence: 99%
“…Such acids can be thought of as the conjugate acid of the WCA formed by the loss of ap roton, and can achieve high Brønsted acidity.T he strength of the underlying Lewis acid is integral to the formation of acorrespondingly strong Brønsted acid, therefore,t he use of the strong Lewis acids B(C 6 F 5 ) 3 and Al-(OR F ) 3 prevails in the literature. [154] Therelated aqua complex H 2 O!B(C 6 F 5 ) 3 has received attention in the literature [254,255] and has been shown to be capable of protonating (and hence oxidizing) metallocene M(Cp) 2 complexes (where M = Cr,F e, or Co). [248] Angewandte Chemie Reviews shown to be as trong enough Brønsted acid to protonate an amido group of M(NR 2 ) 4 (where M = Ti or Zr;R= Me or Et).…”
Section: Conjugate Acidsmentioning
confidence: 99%